Clinical Importance of Sarcopenia And How It Impacts Orthopaedic-Trauma Patients and The Surgical Outcomes - Fauzi, Ahmad; Idrial, David; Asdi, Akbar Rizki Beni (Folia Medica Indonesiana, 2022)
Highlights: • Sarcopenia can cause deleterious effects on patients. • The Asian Working Group for Sarcopenia (AWGS) and the European Working Group on Sarcopenia in Older People (EWGSOP) provide the most widely used criteria to diagnose sarcopenia. • Knowledge of sarcopenia should be a trigger for clinicians and surgeons to evaluate the treatment plan and anticipate the implications experienced by the patients. Abstract: Sarcopenia is a condition of low muscle strength, mass, and low physical performance that is affected by age (primary sarcopenia) and one or combination of systemic diseases, physical inactivity, and insufficient intake of energy (secondary sarcopenia). This condition affects one in ten healthy adults aged â‰¥60 years. There are two widely used criteria to diagnose sarcopenia, the Asian Working Group for Sarcopenia (AWGS) and the European Working Group on Sarcopenia in Older People (EWGSOP). These working groups created algorithms to facilitate the diagnosis. Establishing the diagnosis is crucial because it has deleterious impacts on patients, such as increasing risks of mortality, morbidity, falls, complications during and after surgery, disability, prolonged hospitalization, and fractures. Sarcopenia is considered an independent mortality risk. It is paramount for physicians to assess this condition before treating the patients because it can predict the risk and plan better treatment options to achieve better outcomes. Early assessment is crucial, even for surgeons. Sarcopenia also negatively impacts patients who had surgery. Up to 44% patients who underwent orthopedic trauma surgery had sarcopenia. The high percentage was affected by the increased risk of falls and fractures. On that account, this condition needs to be treated. The main treatments for this condition are exercise dan adequate nutrition intake. The recommended exercise as a first-line treatment is resistance or strength training. Overall, knowledge on sarcopenia can prepare clinicians and surgeons in anticipating the implications of sarcopenia.